Who knows about U = U? Social positionality and knowledge about the (un)transmissibility of HIV from people with undetectable viral loads. Issue 6 (3rd June 2022) - Card, Kiffer G.; St. Denis, Finn; Higgins, Rob; Klassen, Benjamin; Ablona, Aidan; Rutherford, Leo; Jollimore, Jody; Ibáñez-Carrasco, Francisco; Lachowsky, Nathan J.
ABSTRACT: "U = U" is the principle that HIV is untransmittable from people living with an undetectable HIV viral-load. Wide-spread knowledge about U = U is believed to produce public health benefit by reducing HIV-related stigma – promoting wellbeing for people living with HIV. Therefore, we examined the diffusion of U = U with respect to the social position of sexual and gender minority men (SGMM). Participants were SGMM recruited from 16 LGBTQ2S+ pride festivals across Canada. Social position was measured using an index assessing whether participants were (a) trans, (b) a person of colour, (c) Indigenous, (d) born abroad, (e) bisexual or straight, (f) not out, (g) struggling with money, (h) not college educated, (i) and not participating in LGBTQ2S+ Organizations, Queer Pop-ups, or HIV advocacy organizations. Multivariable logistic regression tested whether Index Scores were associated with knowledge about U = U. Among 2681 participants, 72.6% knew about U = U. For HIV-negative/unknown status SGMM, each 1-point increase in Social Positionality Index Scores was associated with a 21% reduction in the odds that they knew about U = U (aOR: 0.79 [0.73, 0.85], per 1-point increase). Results indicate that social marginalization harms the diffusion of HIV-related biomedical knowledge, independent of risk-taking behaviour and other factors.